MILLENNIAL EMPLOYEES’ PERSPECTIVES ON HYBRID WORKING AND ENGAGEMENT IN BAIK INSTITUTE - Ridwan, Muhamad (JURNAL ASIK, 2025)
This study explores how hybrid working shapes employee engagement among millennial employees at BAIK Institute, focusing on their experiences, influencing factors, and perceptions of work relationships. The research employs a qualitative, exploratory approach utilizing purposive sampling and semi-structured interviews to gather rich, descriptive data. The study finds that hybrid work offers millennials meaningful flexibility and autonomy, enabling better work-life balance and higher motivation. The blend of remote and in-person work supports both deep individual focus and essential social interaction, fostering job satisfaction and a strong sense of belonging. Key factors supporting engagement include autonomy, effective communication, empathetic leadership, technological support, and structured social connection practices. While hybrid models offer flexibility, challenges such as communication barriers, social isolation, and balancing work-life boundaries persist. The study emphasizes the indispensable role of inclusive leadership and transparent policies in maintaining relational quality and team cohesion. Recommendations focus on building clear communication channels, leadership training, technological equity, and opportunities for social connection to sustain millennial engagement in hybrid settings. The findings contribute practical insights for organizations seeking to optimize hybrid work systems, highlighting the need for deliberate strategies that align with millennial values and foster an inclusive, motivated workforce in evolving work environments.